MOTIVASI BELAJAR BAHASA INGGRIS PADA MAHASISWA SEKOLAH TINGGI PASTORAL SANTO PETRUS KEUSKUPAN ATAMBUA - Sesfao, Marianus (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2025)
This article describes the motivation to learn English for students of Saint Peter Pastoral College of Atambua Diocese, where there is still a mindset that they are prepared to become Catholic Religious Education teachers, not English teachers. As a result, English, which is a unifying language in the international world, is less attractive to students. The purpose of this study is to determine the level of motivation to learn English for students at Saint Peter Pastoral College of Atambua Diocese. This study apply the descriptive qualitative research design. The subjects of this study were several batches of students at the Saint Peter Pastoral College of Atambua Diocese consists of 100 students from four decanates (Belu, Malaka, Kefamenanu, and Mena) in the Atambua Diocese area and 25 students represent each decanate as samples. The data shows that there were 25 (100%) respondents from Belu decanate who found English is interesting, they get motivated to learn and use it to interact, 24 (94%) students from Malaka decanate, 19 (76%) students from Kefamenanu decanate and 19 (76%) students from Mena decanate who found English as an interesting subject to learn. As conclusion, the sample of 25 students from the Belu decanate (100%) all have higher motivation in learning English and can apply it in daily communication.